Study on the Influence Characteristics of Excavation Face Instability of New Tunnels Orthogonally Crossing Existing Tunnels - Shaokun Ma; Zhang Zhou; Zhibo Duan; Zhen Huang; Benfu He; Pengtao An; Jinmei Li (Applied Sciences)
This study aims to solve the problem of stability of the excavation surface of a new tunnel crossing an existing tunnel orthogonally. The relative horizontal spacing between the two tunnels is taken as an influencing factor, and transparent soil model tests are conducted and expanded with numerical simulations. Finally, the active destabilization mechanism and influence characteristics of the excavation surface of the two tunnels at different horizontal spacings, vertical spacings, and tunnel diameter ratios are obtained. The results show that when the excavated face is destabilized, the existing tunnel located in front of and above the excavation surface limits the development of the upper “silo” and the transfer of soil stress in the destabilized area, and the ultimate support pressure is reduced by 17.6% and 8.7%, respectively. This effect increases as the vertical spacing between the two tunnels decreases and the tunnel diameter ratio increases. At this point, the deformation trend of the existing tunnel cross-section is reflected as “elliptical-shaped”. This trend is more apparent when the vertical spacing between the two tunnels and the tunnel diameter ratio are decreased. The protection of the existing tunnel should be strengthened at this time.